Genomic evidence for the first symbiotic Deferribacterota, a novel gut symbiont from the deep-sea hydrothermal vent shrimp Rimicaris kairei - Qi, Li; Shi, Mengke; Zhu, Fang-Chao; Lian, Chun-Ang; He, Li-Sheng (Frontiers in Microbiology, 2023)
The genus Rimicaris is the dominant species living in hydrothermal vents. However, little research has been done on the functions of the intestinal flora. Here, we investigated the potential functions of Deferribacterota, which is dominant in the intestine of Rimicaris kairei from the Central Indian Ridge. In total, six metagenome-assembled genomes (MAGs) of Deferribacterota were obtained using the metagenomic approach. The six Deferribacterota MAGs were clustered into a new branch based on phylogenetic analysis and then further classified into three species, including one new order and two new genera, based on the phylogenetic analysis, relative evolutionary divergence (RED) and average nucleotide identity (ANI) values. The results of the energy metabolism study showed that these bacteria can use a variety of carbon sources, such as glycogen, sucrose, salicin, arbutin, glucose, cellobiose, and maltose. In addition to glycolysis, Def-MAGs could use acetate or lactate as substrates to enter the gluconeogenesis process, showing their strong energy production ability. These bacteria have a type II secretion system and effector proteins that can transport some intracellular toxins to the extracellular compartment and a type V CRISPR‒Cas system that can defend against various invasions. In addition, cofactors such as biotin, riboflavin, flavin mononucleotide (FMN), and flavin adenine dinucleotide (FAD) synthesized by R. kairei gut Deferribacterota may also assist their host in surviving under extreme conditions. Taken together, Deferribacterota occupied a higher ecological niche in the hydrothermal R. kairei gut after long-term coevolution with the host.